2016
DOI: 10.1536/ihj.16-029
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Aortitis

Abstract: SummaryAortitis is broadly divided into infectious and non-infectious etiologies, each with distinct treatment implications. We present the case of a patient who sustained a type A aortic dissection during urgent coronary angiography for acute coronary syndrome. Clinical findings and events during the procedure raised suspicion for an underlying vascular disorder; however, the diagnosis of staphylococcal aortitis was not made until pathological examination of resected tissue. Clues to the diagnosis of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In previous publications, SA aortitis has been reported 2 5. Our observation adds to this pool of diagnosis and treatment of the SA aortitis, highlighting the importance of early diagnosis and surgical management.…”
Section: Discussionsupporting
confidence: 55%
“…In previous publications, SA aortitis has been reported 2 5. Our observation adds to this pool of diagnosis and treatment of the SA aortitis, highlighting the importance of early diagnosis and surgical management.…”
Section: Discussionsupporting
confidence: 55%
“…Although the major causes of bacterial pericarditis are such as Staphylococcus, 5) Streptococcus, Haemophilus, and Mycobacterium tuberculosis, 6) in this case, purulent pericarditis was caused PURULENT PERICARDITIS BY Escherichia coli by very uncommon gram-negative bacillus, E. coli. The unexpected causative bacteria of E. coli and sudden clinical changes without a premonitory severe symptom were peculiarity of this case.…”
Section: Discussionmentioning
confidence: 71%
“…Disadvantages of MRI include the fact that it is not always available and its unsuitability for patients with implanted devices or who are critically unwell. 8 Recent studies have found 3D-black-blood MRI is an effective and radiation-free alternative to cross sectional CT imaging for the diagnosis of thoracic large vessel vasculitis, making it a useful modality for investigating non-infectious aortitis. 19,20 Both MRI and multi-slice CT imaging are useful in defining the extent of the disease and for planning surgical intervention.…”
Section: Aetiologymentioning
confidence: 99%
“…Despite having been the investigation of choice in the past, angiography is invasive and poses the risk of causing the rupture of the aortic wall which can be very fragile when inflamed. 8 As such, it remains useful only in situations where aortitis or a mycotic aneurysm cannot be excluded otherwise. 11 Similarly, ultrasound scanning (US) is not a commonly used modality for diagnosing aortitis, but abdominal or transthoracic US can show circumferential thickening of the aortic wall and can be useful in identifying and assessing aneurysms in the ascending thoracic aorta.…”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation